Association between heart rate variability and haemodynamic response to exercise in chronic heart failure. (4th March 2019) - Koshy, Aaron; Okwose, Nduka C.; Nunan, David; Toms, Anet; Brodie, David A.; Doherty, Patrick; Seferovic, Petar; Ristic, Arsen; Velicki, Lazar; Filipovic, Nenad; Popovic, Dejana; Skinner, Jane; et al.
Abstract: Objectives. Heart rate variability (HRV) and haemodynamic response to exercise (i.e. peak cardiac power output) are strong predictors of mortality in heart failure. The present study assessed the relationship between measures of HRV and peak cardiac power output. Design. In a prospective observational study of 33 patients (age 54 ± 16 years) with chronic heart failure with reduced left ventricular ejection fraction (29 ± 11%), measures of the HRV (i.e. R-R interval and standard deviation of normal R-R intervals, SDNN) were recorded in a supine position. All patients underwent maximal graded cardiopulmonary exercise testing with non-invasive (inert gas rebreathing) cardiac output assessment. Cardiac power output, expressed in watts, was calculated as the product of cardiac output and mean arterial blood pressure. Results. The mean RR and SDNN were 837 ± 166 and 96 ± 29 ms, peak exercise cardiac power output 2.28 ± 0.85 watts, cardiac output 10.34 ± 3.14 L/min, mean arterial blood pressure 98 ± 14 mmHg, stroke volume 91.43 ± 40.77 mL/beat, and oxygen consumption 19.0 ± 5.6 mL/kg/min. There was a significant but only moderate relationship between the RR interval and peak exercise cardiac power output ( r = 0.43, p = .013), cardiac output ( r = 0.35, p = .047), and mean arterial blood pressure ( r = 0.45, p = .009). The SDNN correlated with peak cardiac power output ( r = 0.42, p = .016), mean arterial blood arterial ( r = 0.41, p = .019), and stroke volume ( r = 0.35, p = .043). Conclusions. Moderate strength of the relationship between measures of HRV and cardiac response to exercise suggests that cardiac autonomic function is not good indicator of overall function and pumping capability of the heart in chronic heart failure.